DESIGN OF SOFTWARE APPLICATION FOR LEARNING MATHEMATICS CLASS I AND CLASS II ELEMENTARY SCHOOL - Emi Sudaryanti; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2006)
Developments in science and technology allows all parties can obtain abundant information, quickly and easily from various sources and places in the world. Thus students need to have the ability to acquire, select and manage information to survive in an ever-changing circumstances, uncertain and competitive. This capability requires critical thinking, systematic, logical, creative and effective willingness to cooperate. This kind of thinking can be developed through the learning of mathematics because mathematics has a structure and a strong and clear linkage between the concept that allows us to skillfully think rationally. As we all know math is one of the subjects that are less enthused by learners until there is a tendency to follow the fear of maths because it is very difficult to understand. One way to get students interested and not afraid to learn mathematics is to make a computer software application that can be used easily and with displays that can attract students to study mathematics.